2017
DOI: 10.1111/jpn.12807
|View full text |Cite
|
Sign up to set email alerts
|

In ovo feeding of carbohydrates for broilers—a systematic review

Abstract: SummaryThe purpose of this systematic review was to evaluate the evidence that the injection of carbohydrate-based solutions into embryonated eggs improves broiler performance. A literature search was conducted in April 2017 using the keywords broiler, carbohydrate, in ovo, nutrition and poultry. Only papers that involved in ovo carbohydrate injections in poultry were used in this study. After specific selection criteria, 17 papers were selected. The quality scoring system of the selected studies was based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 21 publications
0
18
0
6
Order By: Relevance
“…In addition, the present study did not include a non‐injected group, which would allow evaluating the effect of the IOF technique. In a review, Retes et al () observed a reduction of 17% in hatchability in IOF studies using saline solution as diluent, compared with intact eggs. Even without a non‐injected group, we can observe that the glycerol used in the current concentrations did not show embryotoxicity, since the percentage of embryo death after inoculation was not different among saline and glycerol solutions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the present study did not include a non‐injected group, which would allow evaluating the effect of the IOF technique. In a review, Retes et al () observed a reduction of 17% in hatchability in IOF studies using saline solution as diluent, compared with intact eggs. Even without a non‐injected group, we can observe that the glycerol used in the current concentrations did not show embryotoxicity, since the percentage of embryo death after inoculation was not different among saline and glycerol solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Une surexpression des gènes liés à l'atrophie tels que l'atrogine-1 et le MuRF1 observée à l'éclosion par rapport au jour 18 de l'embryogenèse pourrait expliquer partiellement cette fonte du muscle pectoral (Everaert et al, 2013). Pour limiter l'utilisation des acides gras et la protéolyse des protéines musculaires à des fins énergétiques, des injections de carbohydrates seuls ou associés à d'autres nutriments d'intérêt ont été réalisées in ovo (Retes et al, 2018).…”
Section: Enrichissement De L'oeuf En Substrats éNergétiquesunclassified
“…La supplémentation in ovo a eu souvent pour objectif d'augmenter la quantité de sucres disponible dans l'oeuf et ainsi d'épargner l'utilisation d'acides aminés pour la gluconéogenèse (Kornasio et al, 2011). Retes et al (2018) a pu ainsi démontrer dans une synthèse récente que les résultats étaient à la fois dépendants du type de sucre injecté, du site d'injection (vitellus, albumen, amnios, liquide allantoïque ou chambre à air), du stade de développement de l'embryon et de la génétique à laquelle les études s'intéressent. Uni et al (2005), par exemple, ont montré que l'administration à 17,5 jours d'une solution contenant des hydrates de carbone (maltose, saccharose, dextrine) et un métabolite de la leucine (β-hydroxy-méthylbutyrate) augmentait le poids des poussins à l'éclosion de 5 à 6 %, ainsi que les réserves de glycogène hépatique de 2 à 5 fois et rendement du muscle pectoral de 6 à 8 % par rapport à des poussins témoins dont les oeufs n'ont pas été supplémentés.…”
Section: Enrichissement De L'oeuf En Substrats éNergétiquesunclassified
“…현재 전 세계적으로 사육되고 있는 대부분 육계는 조기성 장을 목적으로 개량되었으며, 도계 일령은 대부분 35∼42일 령이 된다. 이러한 사육기간을 고려하면, 배아시기의 21일 은 도계 직전까지의 약 33∼38%의 삶을 차지한다 (Retes et al, 2018). 근육과 같은 조직의 이른 시기 발달을 고려하면, 배아의 발달과 부화 후 육계의 능력은 강한 상관관계가 있 다 (Grodzik et al, 2013).…”
Section: 부화전후 미생물 균총의 변화와 In Ovo Feedingunclassified